Promoting Oral Mucosal Wound Healing with a Hydrogel Adhesive Based on a Phototriggered S‐Nitrosylation Coupling Reaction. Issue 48 (4th October 2021) - Zhang, Wenjie; Bao, Bingkun; Jiang, Fei; Zhang, Yiqing; Zhou, Renjie; Lu, Yuezhi; Lin, Sihan; Lin, Qiuning; Jiang, Xinquan; Zhu, Linyong
Abstract: The wet and highly dynamic environment of the mouth makes local treatment of oral mucosal diseases challenging. To overcome this, a photo‐crosslinking hydrogel adhesive is developed inspired by the success of light‐curing techniques in dentistry. The adhesive operates on a fast (within 5 s) phototriggered S‐nitrosylation coupling reaction and employs imine anchoring to connect to host tissues. Unlike other often‐used clinical agents that adhere weakly and for short durations, this thin, elastic, adhesive, and degradable cyclic o ‐nitrobenzyl‐modified hyaluronic acid gel protects mucosal wounds from disturbance by liquid rinsing, oral movement, and friction for more than 24 h. The results from both rat and pig oral mucosa repair models demonstrate that this new gel adhesive creates a favorable microenvironment for tissue repair and can shorten tissue healing time. This study thus illustrates a therapeutic strategy with the potential to advance the treatment of oral mucosal defects in the clinic. Abstract : Based on a new coupling reaction, an easily operated hydrogel adhesive that features thin‐layer fabrication, ultrafast gelation, appropriate elasticity, and excellent tissue adhesion is developed. This hydrogel adhesive matches the material requirements for oral mucosal treatment and establishes a conducive microenvironment for tissue growth, thus notably shortening the healing time of mucosal wounds.